On Quasi-Small Prime Submodules - Ali, Wisam A.; Mothafar, Nuhad S. Al. (Iraqi Journal of Science, 2022)
Let  be a commutative  ring with identity , and  be a unitary (left) R-module. A proper submodule  of  is said to be quasi- small prime submodule  , if whenever   with  and , then either or . In this paper ,we give a comprehensive study of quasi- small prime submodules.